Duta Versus Ulama - fitriah fitriah (Medina-te : Jurnal Studi Islam, 2017)
In the era of the early 60's the city of Kayuagung, which was the capital of the Regency of Ogan Komering Ilir (OKI), was very well known for its nickname as the area of ​​the Koran because the city gave birth to many reciters and tahfidz. Along with the development of time, the nickname finally experienced a shift. Kayuagung, formerly known as the Qur'anic region, which has created hafizh and reciters' cadres, has changed its image to become an exporter of foreign ambassadors or bandits whose work is of course related to the world of crime, such as pickpocketing, stealing and grabbing. Although according to Islamic teachings, the actions and behavior of these ambassadors are classified into acts that are prohibited and contrary to the rules contained in the texts of the al-Quran and Hadits, but in reality in social reality, many religious phenomena that contribute to and complement its existence as a criminal as well as a Muslim who obeys his religion.